A Statistical Survey of Radiation Belt Dropouts Observed by Van Allen Probes - Zheng Xiang; Weichao Tu; Binbin Ni; M. G. Henderson; Xing Cao (Geophysical Research Letters, 2018)
Abstract A statistical analysis on the radiation belt dropouts is performed based on 4 years of electron phase space density data from the Van Allen Probes. The μ, K, and L* dependence of dropouts and their driving mechanisms and geomagnetic and solar wind conditions are investigated using electron phase space density data sets for the first time. Our results suggest that electronmagnetic ion cyclotron (EMIC) wave scattering is the dominant dropout mechanism at low L* region, which requires the most active geomagnetic and solar wind conditions. In contrast, dropouts at high L* have a higher occurrence and are due to a combination of EMIC wave scattering and outward radial diffusion associated with magnetopause shadowing. In addition, outward radial diffusion at high L* is found to cause larger dropouts than EMIC wave scattering and is accompanied with active geomagnetic and solar wind drivers.